Ambitious like a mother : why prioritizing your career is good for your kids - Bazelon, Lara, 1974- (Little, Brown Spark, 2022)
A law professional argues that women prioritizing their career benefits mothers, kids, and society at large by showing how they can use their talents to help others and raise awareness about issues that are important to them.